EFFECT OF MEFENAMIC ACID TO ACUPUNCTURE THERAPY ON CARRAGEENAN-INDUCED INFLAMMATORY PAIN IN THE HIND LIMB OF THE RAT - Mercya, Yovita
Non steroidal anti-inflammatory drug (NSAID), such as mefenamic acid, works by inhibiting the formation of inflammatory mediators, the prostaglandins. On the contrary, the analgesic acupuncture can increase the pain threshold by increasing the formation of inflammatory mediators locally, followed by the increased secretion of endorphins. The purpose of this study is to compare the effectiveness of NSAID, acupuncture, and their combination on the improvement of inflammatory pain. The study begins with collecting the data use a set of questionnaire containing scores of Visual Analogue Rating Scale (VAS) to assess the effectiveness of NSAIDs and GI acupuncture for patients with inflammatory pain who used NSAIDs at the beginning and then switched to GI acupuncture. The results of this clinical study then continued with the design of experimental studies to see the effectiveness of mefenamic acid to acupuncture therapy in 24 male Wistar rats that got intraplantar induced of carrageenan. The experimental animals were divided into six groups: pain control group, mefenamic acid group, beforeinduction acupuncture group, after-induction acupuncture group, before-induction acupuncture & mefenamic acid combination group, and after-induction acupuncture & mefenamic acid combination group. The data measured in this study is inflammatory volume (measure with plethysmometer) and pain thre>hold (measure with dolorimeter). Inflammation and pain threshold is done every 60hninutes during six hours after induction of carrageenan. The results of the questionnaire data processing in patients showed an average reduction in VAS score of GI acupuncture is significantly greater compared with NSAIDs (3.20 ± 0.7 vs 2.43 ± 0.998) proved by the value of p = 0.000 (p <0.05). Results of animal studies showed an improvement of inflammatory pain, characterized by the significantly decrease of inflammatory volume or the significantly increase of the pain threshold between all treatment groups with the control pain group (p <0.05) except for the after induction acupuncture group. The decrease of inflammation volume in before-induction acupuncture group significantly greater than mefenamic acid groups, however the increase in pain threshold mefenamic acid group significantly greater than the before-induction acupuncture group. Before induction acupuncture mefenamic acid group (inflammation inhibition value 40.24%; pain inhibition value 8.95%) showed a significantly smaller value (p <0.05) in reducing inflammation and increasing the pain threshold compared to single mefenamic acid group (inflammation inhibition value 58.53%; the pain inhibition value 09.09%) and single acupuncture therapy before induction (inflammation inhibition value 78.04%; the pain inhibition value 23.07%). The conclusion of this study are single mefenamic acid or acupuncture therapy may improve inflammatory pain, but the administration of mefenamic acid degrade the effectiveness of acupuncture therapy in addressing inflammatory pain.